2018
DOI: 10.7717/peerj.4849
|View full text |Cite
|
Sign up to set email alerts
|

A survey on sleep assessment methods

Abstract: PurposeA literature review is presented that aims to summarize and compare current methods to evaluate sleep.MethodsCurrent sleep assessment methods have been classified according to different criteria; e.g., objective (polysomnography, actigraphy…) vs. subjective (sleep questionnaires, diaries…), contact vs. contactless devices, and need for medical assistance vs. self-assessment. A comparison of validation studies is carried out for each method, identifying their sensitivity and specificity reported in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
167
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(184 citation statements)
references
References 62 publications
2
167
0
2
Order By: Relevance
“…Nevertheless, our study further found that data accuracy, despite of being a key concern in sleep research, is not necessarily a key concern when people assess the credibility of technology. In the domain of sleep medicine, sleep diaries or questionnaires that measure subjective sleep experience are routinely ranked lower than any kind of sleep-tracking devices-either contactless devices, contact devices or PSG-with respect to accuracy [42]. However, our study shows that approximately a third of the participants gave higher credence to their subjective experience over data, and another third acknowledged the importance of both subjectivity and objectivity.…”
Section: Four Levels Of Credibility Assessmentmentioning
confidence: 60%
“…Nevertheless, our study further found that data accuracy, despite of being a key concern in sleep research, is not necessarily a key concern when people assess the credibility of technology. In the domain of sleep medicine, sleep diaries or questionnaires that measure subjective sleep experience are routinely ranked lower than any kind of sleep-tracking devices-either contactless devices, contact devices or PSG-with respect to accuracy [42]. However, our study shows that approximately a third of the participants gave higher credence to their subjective experience over data, and another third acknowledged the importance of both subjectivity and objectivity.…”
Section: Four Levels Of Credibility Assessmentmentioning
confidence: 60%
“…However, ESS is still the most used sleepiness score in clinical practice worldwide; for better efficiency, as we did for our SAS score , it is usually combined with other objective measurements [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Objective assessment of the usual body activity, in terms of energy consumed, may derive from actigraphy, which is a non-invasive method for monitoring rest/activity cycles. 81 To record physical activity, actigraphy devices (eg, single or multiple axis accelerometers) are usually worn on the wrist to record movements that can be used to estimate wavering parameters with the support of computerized algorithms. Subjective questionnaires may also be useful in order to obtain a different perceptive information, but they show more variability in properties of methodological effectiveness than objective measures, 82 such as accelerometer/activity monitor, as the latter allows examining the motion in free-living environments.…”
Section: Existing Methods To Assess Physical Activity Levelsmentioning
confidence: 99%